POTENSI Musca domesticaLinn. SEBAGAI VEKTOR BEBERAPA PENYAKIT - Hastutiek, Poedji; Fitri, Loeki Enggar (Fakultas Kedokteran Universitas Brawijaya, 2007)
Musca domestica is a fly which can be found aroundhouse and cage. Its present interference human hygiene, calmness and health. This fly generating many loss at human being and animal because this fly have high potency in spreading many diseases agents, that are protozoa, worm, virus, bacterium and fungi. Several agents of emerging,reemerging and new emerging diseases can be transferred by M. domestica such as Cryptosporidium parvum, Helicobacter pylori, E.coli O157:H7 and H5N1. Agens removed by M. domestica through regurgitasi, excrete and exoskleleton. Interestingly M. domestica might be act as biological vector. Key words: Musca domestica, agent of disease